A categoria de aspecto em algumas línguas indígenas do Brasil - De Souza, Edson Rosa Francisco [UNESP]; De Oliveira, Lucas Marques [UNESP] (Universidade Estadual de Maringa, 2017)
The aim of the paper is to analyze, from the Functional Discourse Grammar perspective, FDG (Hengeveld and Mackenzie, 2008), the notions of aspect in the indigenous languages of the families Arawak (Kinikinau), Jê (Parkatejê, Xerente and Xavante), Guató (Guató) Tupi-Guarani (Asurini) Boróro (Boróro) Karib (Ikpeng), Pano (Katukina, Matis and Shanenawa) and Ofayé (Ofayé), taking into account the ordering of the categories of tense, aspect and mood (TAM) with respect to the predicate and the semantic scope relations among these grammatical categories according to the levels and layers of the FDG. As a result, we found that the qualitative aspect (perfective, imperfective and so on) tends to be placed closer to the verb, by affecting the internal temporal constitution of the state-of-affairs, while the quantitative aspect (habitual) and tense tend to stand farther from the predicate, by modifying the state-of-affairs as a whole. The mood notions tend to be placed more distant from the verb, since they not directly affect the verb. We also verified that the distribution of TAM categories respects, in general, the ordering and the scope relations among them, as proposed by Hengeveld (2011) in: (mood(tense(aspect(predicate+arguments)))).
The category of aspect in some native languages of Brazil
Keywords: Aspect; FDG; Implicational hierarchies; Indigenous languages